Emergency remote teaching experience: Challenges, actions and suggested measures of STEM research teachers in Pangasinan Philippines - Mark Angelbert B. Dulay; Shielmyn Kate J. Manuel (International Research Journal of Science, Technology, Education, and Management, 2021)
The Department of Education (DepEd) resorts to using Self-Learning Modules (SLM) with the alternative learning delivery modalities for various types of learners across the Philippines. This sudden change in the methodology of teaching is commonly known as Emergency Remote Teaching (ERT). Emergency Remote Teaching is a shift of delivering lessons due to crisis. This phenomenological qualitative research aims to determine the experiences of STEM Research teachers during Emergency Remote Teaching. On this premise, a phenomenological research design was conducted among the STEM Research teacher of Pangasinan Province, Philippines. The researchers seek information on the difficulties encountered, actions taken, and suggested measures of the STEM research teachers using an interview method. The participants were selected by the researchers via purposive convenience sampling since the study was conducted in the middle of a pandemic. Interview questions were done online and phone calls upon the availability of the respondents. The data were interpreted and analyzed after participants shared their experiences as research teachers at the time of the pandemic. The results reveal the following statements. The student’s struggle of understanding the lesson and delivery of instruction is the main difficulties experienced by the respondent-teachers. This is supported by technical difficulties and struggle in monitoring and evaluation. The actions taken by the teacher-respondents to address this were constant and use of different modes of communication. This includes individual consultation and the use of blended learning. The research teachers suggested measures for the stakeholders are the organization of training and creating unified learning materials. While the teacher-respondents also suggested stakeholders’ investment in scientific research.